2008
DOI: 10.1308/003588408x242123
|View full text |Cite
|
Sign up to set email alerts
|

Ureteric Stent Card Register – A 5-Year Retrospective Analysis

Abstract: INTRODUCTION Ureteric stenting is a common urological procedure. Forgotten stents have a well-documented morbidity and mortality. Therefore, we asked the question, is a stent register an important factor in reducing the number of lost or overdue stents? PATIENTS AND METHODS We conducted a retrospective review of 203 patients who had ureteric stents inserted in the operating theatre, for the 5-year period 1 December 1998 to 1 December 2003. We analysed all stent cards, patient notes and theatre logs; where no r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 9 publications
0
30
1
Order By: Relevance
“…17 Tang VC et al studied the stent card system to track the retained DJ stent and have proposed the computerized DJ stent registry and similarly Lynch MF et al in their study showed the importance of electronic stent register and stent extraction reminder facility to avoid the DJ stent follow up loss and avoid the morbidity associated with it. 18,19 McCahy et al recommended that a computer record should be made recording the patients that stent was placed in urology clinics and warning and informing the urology physicians about the time of removal of stents. 20 Stents on strings have been proposed where one end of the stent is tied to a sting, which is externalized for easy removal later.…”
Section: Discussionmentioning
confidence: 99%
“…17 Tang VC et al studied the stent card system to track the retained DJ stent and have proposed the computerized DJ stent registry and similarly Lynch MF et al in their study showed the importance of electronic stent register and stent extraction reminder facility to avoid the DJ stent follow up loss and avoid the morbidity associated with it. 18,19 McCahy et al recommended that a computer record should be made recording the patients that stent was placed in urology clinics and warning and informing the urology physicians about the time of removal of stents. 20 Stents on strings have been proposed where one end of the stent is tied to a sting, which is externalized for easy removal later.…”
Section: Discussionmentioning
confidence: 99%
“…Tang et al 12 emphasize that patients should take an active role in the monitoring and management of their catheters, a situation that is not always possible due to the socioeconomic and cultural conditions of patients due to the context in which the catheters are implanted, often after intraoperative complications of surgeries performed by specialties other than urology. Most of the catheters are placed in medical centers that have a considerable flow of patients where monitoring is frequently by other medical teams such as gynecology, proctology and oncology.…”
Section: Discussionmentioning
confidence: 99%
“…However, recognizing the inadequacy of this system, the authors recommended using a new system that included a patient education leaflet and a stent removal date that was planned prior to his/her discharge from the hospital [6]. Tang et al [7] retrospectively analyzed patients who had received stents within the previous 5 years and emphasized that their specific stent card tracking systems were ineffective during monitoring because of infrequent revisions and difficulties in updating the system. The failure of these systems was attributed to the fundamental problem of human negligence when registering patients, while the importance of successfully applying computerized systems that minimize human error was also emphasized.…”
Section: Discussionmentioning
confidence: 99%
“…In this system, all of the responsibility is with the attending surgeon. Tang et al [7] emphasized that the patients must assume an active role in the monitoring and management of their stents. In our system, short reminder messages and information are sent to both patients and physicians.…”
Section: Discussionmentioning
confidence: 99%